The efficacy of topical treatments for acanthosis nigricans: a systematic review of randomized controlled trials - Alamri, Awadh; Alraddadi, Rose A.; Alzahrani, Dhaii; Abualola, Amal H.; Maaddawi, Hadeel A.; Alharthy, Renad F.; Alkhashan, Alanoud Y.; Ashqan, Maria Y.; Shaheen, Esraa A.; Almahdi, Bashaer; Althobaiti, Hatoon M. (Frontiers in Medicine, 2025)
BackgroundAcanthosis nigricans (AN) is a skin disorder marked by darkening and thickening of the skin, often linked to metabolic abnormalities. This systematic review of randomized controlled trials (RCTs) assesses the comparative effectiveness and tolerability of different topical treatment options of AN, aiming to determine the most suitable therapeutic strategies.MethodsA comprehensive literature search was conducted across PubMed, Scopus, ClinicalTrials.gov, Web of Science, and the Cochrane Library, yielding 6,407 studies. After screening and a full-text review, seven randomized controlled trials (n = 268) assessed topical urea (10–20%), tretinoin (0.025–0.05%), salicylic acid (10%), and chemical peels such as glycolic acid (35–70%) and trichloroacetic acid (15%) over 8 weeks to 2 months, primarily on the neck and axilla. Outcomes included melanin and erythema indices (M/E), ANASI/ANSC scores, Investigator’s and Participant’s Global Evaluation (IGE/PGE), and adverse events.ResultsUrea demonstrated significant efficacy in reducing erythema, particularly at higher concentrations (20%), with mild adverse events such as stinging or irritation. Tretinoin was the most effective for reducing dark pigmentation, especially on the neck, and patients were more satisfied with it than with glycolic acid. Salicylic acid (10%) gave results similar to urea, with only mild side effects like dryness or peeling. Trichloroacetic acid (15%) peel was more effective than glycolic acid (35%) peel, both in skin improvement and patient satisfaction after 8 weeks. Overall, side effects with all treatments were mild and went away on their own.ConclusionBoth urea and tretinoin are effective treatments for AN, choice of therapy should be individualized tretinoin for predominant hyperpigmentation, urea for erythema or lower irritation tolerance, salicylic acid as a tolerable alternative, and TCA peel when stronger procedural options are suitable glycolic peel showed more modest effects.Systematic review registrationProspero registration number: (CRD42023444441); https://www.crd.york.ac.uk/PROSPERO/view/CRD42023444441.